2009
DOI: 10.1186/1471-2229-9-47
|View full text |Cite
|
Sign up to set email alerts
|

Transient effect of weak electromagnetic fields on calcium ion concentration in Arabidopsis thaliana

Abstract: Background: Weak magnetic and electromagnetic fields can influence physiological processes in animals, plants and microorganisms, but the underlying way of perception is poorly understood. The ion cyclotron resonance is one of the discussed mechanisms, predicting biological effects for definite frequencies and intensities of electromagnetic fields possibly by affecting the physiological availability of small ions. Above all an influence on Calcium, which is crucial for many life processes, is in the focus of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 36 publications
0
27
0
1
Order By: Relevance
“…Elevated concentrations of free cytosolic calcium are induced in response to various stimuli, such as red light, mechanical stimulation, cold shock, gravity, pathogen attack, phytohormones, drought and salinity (Toyota et al, 2008;Song et al, 2009). The monitoring of the bioluminescence of aequorin in Arabidopsis thaliana (Pazur and Rassadina, 2009) showed that combinations of magnetic and electromagnetic fields caused temporary changes in the internal Ca 2+ concentrations and that this phenomenon can be explained according to ion cyclotron resonance. However, the decreased total calcium content of the MF-treated maize plants in the present study is better explained according to the beneficial effects of the combination of the GeoMF and WEMF on the membrane integrity (the crucial sites of channels and pumps) or by the direct effect on the calcium channels and pumps.…”
Section: Resultsmentioning
confidence: 98%
“…Elevated concentrations of free cytosolic calcium are induced in response to various stimuli, such as red light, mechanical stimulation, cold shock, gravity, pathogen attack, phytohormones, drought and salinity (Toyota et al, 2008;Song et al, 2009). The monitoring of the bioluminescence of aequorin in Arabidopsis thaliana (Pazur and Rassadina, 2009) showed that combinations of magnetic and electromagnetic fields caused temporary changes in the internal Ca 2+ concentrations and that this phenomenon can be explained according to ion cyclotron resonance. However, the decreased total calcium content of the MF-treated maize plants in the present study is better explained according to the beneficial effects of the combination of the GeoMF and WEMF on the membrane integrity (the crucial sites of channels and pumps) or by the direct effect on the calcium channels and pumps.…”
Section: Resultsmentioning
confidence: 98%
“…Microwave cell exposure induces an increase in intracellular calcium concentration (Pazur and Rassadina, 2009). An intranuclear increase of calcium concentration has been shown to induce chromatin condensation (Martin and Cardoso, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The calcium concentration increases in cell under the action of EMFs [102,103]. During the chronic exposure the calcium ions are released from the membrane, which are membrane bound and are released into the cytosol [104].…”
Section: The Action Of Emf On Intracellular Regulatory Systemsmentioning
confidence: 99%